Winter Diversity of Birds in Makaibari Tea Estate, Kurseong, Darjeeling, India - Ahmad, Khursheed; Yahya, H. S. A. (Indian Forester, 2010)
This study was carried out in Makaibari Tea Estate between January 20 and March 03, 1998. Makaibari Tea Estate is perhaps the only private land in North-East India, where good protection and management has been accorded to the forest and wildlife in harmony with the villagers. Out of 614 hectares of the total land, belonging to the Tea Estate, 400 hectares is forest and rest is tea plantation. This short-term study in the Tea Estate involved preparation of inventory of the avifauna and intensive data collection on the bird species richness and diversity in various habitats. A total of 130 species of birds were recorded, of which 53 were common.